The role of business models for technology innovation : a case study on Power-to-Gas - Fjellstedt, Tone; Galbraith, Thomas Hill Anderson (SLU/Dept. of Economics, 2021)
The thesis contributes to the understanding of business models as performative market devices for development and uptake of technological innovation in low carbon transitions. Transition studies are criticised for neglecting the role of business models as part of socio-technical transitions. Transition research agendas call for taking a pragmatic view on the role of business models. The thesis draws on a framework, based on the multi-layered perspective that views business models as performative market devices. Business models then act as intermediaries to develop and societal embed an emerging technology innovation into the regime.